Follow-Up Results Of The Bpk Recommendations In Improving The Quality Of Financial Reports At The Main Office Of Harbormaster And Port Authority (Ksop) Belawan - Ariesta, Gobel Gina; Dewi, Husnainy; Sangkot, Khadijah; Yusnita, Nasution; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The Main Office of Harbormaster and Port Authority (KSOP) Belawan is a significant contributor to state revenue, occupying a strategic position by generating Non-Tax State Revenue (PNBP) within the maritime sector. This study aims to analyze the extent to which the implementation of follow-ups on audit recommendations (TLRHP) from the Audit Board of the Republic of Indonesia (BPK) enhances the quality of financial reporting at the KSOP Main Office Belawan. This research employs a descriptive qualitative methodology with a case study approach. Data were collected through documentation of BPK’s Audit Result Reports (LHP) and follow-up monitoring reports for the 2022–2023 period, as well as in-depth interviews with relevant units. The findings reveal that the implementation of follow-ups at KSOP Main Office Belawan serves to strengthen the Internal Control System (SPI) and maintain compliance regarding PNBP deposits. When recommendations are effectively resolved, recurring findings are minimized, fixed asset data becomes more reliable, and revenue recording becomes more accurate, ultimately supporting the attainment of an Unqualified Opinion (WTP) at the Ministry of Transportation level. The primary obstacles identified include the complexity of port service tariff regulations and administrative barriers regarding land assets.